Airway Pressure Gradient May Decrease the Beating Amplitude of Cilia - George, Uduak Z.; Pidaparti, Ramana M. (Frontiers in Physics, 2019)
Motile cilia reside on the surface of the epithelial layer of the lungs and facilitates the clearance of mucus in the airways. Bordering the epithelial layer and surrounding cilia is the periciliary liquid (PCL) that lubricates the epithelial layer. In the present work, we propose a novel approach to study how changes in biomechanics affect the physiological functioning of cilia in healthy subjects and in patients with CF, COPD, and primary ciliary dyskinesia (PCD). In particular, we investigate the response of cilia to different local pressure gradient during gaseous exchange. We hypothesize that the airway pressure gradient that occur during inhalation and exhalation may displace mucus and PCL and exert pressure on cilia. Therefore, cilia must be able to withstand the forces created by the airway pressure gradient, otherwise the magnitude of its efficient strokes and its rate of mucociliary clearance would decrease. We develop a computational model of the airways to quantify the effect of airway pressure gradient on cilia dynamics. In the model, cilia are represented as elastic solids, PCL and mucus is represented as fluids with different viscosities. The simulation results show that in diseases such as PCD, where there exist changes in ciliary structure, the airway pressure gradient may affect the propulsive stroke of cilia and decrease the rate of mucociliary clearance. Simulation results predict that the average stress experienced by cilia varies exponentially with the number of cilia shed from CF and COPD airways.